Case Study: International Fund for Agricultural Development (IFAD) investment in innovation for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
The only specialized multilateral development institution focused exclusively on rural development, IFAD has successfully used agriculture as a means of poverty reduction – contributing ~USD 22 billion in funding to date1 . About 90% of IFAD's portfolio is focused on Low to Middle Income (LMI) countries. IFAD stands out with its nutrition and gender-sensitive lenses coupled with investments in climate resilient agriculture – mainstreaming nutrition, gender, and climate change work in agriculture. An experienced agency in brokering partnerships, IFAD has to date mobilized ~ USD 31 billion in co financing and funding from domestic sources. IFAD’s specialized focus on agriculture with additional lenses, as well as its success with collaborations can inspire many other funders - meriting a deeper look.